A study on green purchase intention towards green consumer at Johor / Siti Nazirah Jumaat and Norhafizah Mohd Hatta - Jumaat, Siti Nazirah; Mohd Hatta, Norhafizah (2014)
The purpose of this study was to investigate the relationship of the selected independent variables: green perceived value, green trust, green perceived risk and green awareness with dependent variable which is green purchase intention. In order to provide a guide in the study, four hypotheses were formulated. Data were collected from 150 respondents using the questionnaire. This study was conducted at Johor Bahru choose randomly and covers all the community without state who are the respondents. Then the results were analyzed by using SPSS to find the significant relationship with the dependent variable. At the end of the study, based from the findings, several recommendations have been made for the organization and also for future research purpose. Through this study, it will help other researcher or manufacturer to identify the new strategy that can be used to encourage consumers to purchase green product to save environment.